Selectfluor TM F-TEDA-BF4 mediated introduction of perfluoroalkyl-containing groups in the benzylic position of hexamethylbenzene - Stavber, Stojan (Acta chimica slovenica, 2002)
An effective synthetic pathway for direct introduction of a perfluoroalkyl moiety- containing functional groups at the benzylic position in hexamethylbenzene involved treatment of 1-chloromethyl-4-fluoro-1,4-diazoniabicyclo2.2.2octane bis(tetra-fluoroborate) (SelectfluorTM F-TEDA-BF4 ) with hexamethylbenzene in the presence of polyfluoro alcohols or potassium salts of perfluoroalkane carboxylic acids.
Keywords: alkiliranje; fluoriranje; heksametilbenzen; kemijske reakcije